2020
DOI: 10.1007/s00277-020-04256-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of hemoglobin level and autoimmune hemolytic anemia in SARS-CoV-2 infection

Abstract: Higher levels of D-dimer, LDH, and ferritin, all have been associated with the poor prognosis of COVID-19. In a disease where there are acute inflammation and compromised oxygenation, we investigated the impact of initial hemoglobin (Hgb) levels at Emergency Department (ED) triage on the severity and the clinical course of COVID-19. We conducted a cross-sectional study on 601 COVID-19 patients in a COVID-19 national referral center between 13 and 27 June 2020. All adult patients presented at our hospital that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 42 publications
2
45
0
6
Order By: Relevance
“…Twelve patients presented with autoimmune hemolytic anemia (AIHA), among them 4 had B lymphoid malignancy, one had monoclonal gammapathy (Jensen et al, 2020;Lazarian et al, 2020;Lopez et al, 2020) and 2 had Evans syndrome (Li et al, 2020;Wahlster et al, 2020). Later, it was stated that AIHA could concern 12% of the subgroup of anemic COVID-19 patients (Algassim et al, 2021). Fourteen additional patients were described: five with paroxysmal nocturnal hemoglobinuria (Kulasekararaj et al, 2020;Pike et al, 2020) and 9 with previously undiagnosed glucose-6-phosphate dehydrogenase (G6PD) deficiency uncovered in context of acute hemolysis (Aguilar and Averbukh, 2020;Beauverd et al, 2020;De Franceschi et al, 2020;Kuipers et al, 2020;Maillart et al, 2020;Palmer et al, 2020;Sasi et al, 2020;Sgherza et al, 2020;Lopes et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve patients presented with autoimmune hemolytic anemia (AIHA), among them 4 had B lymphoid malignancy, one had monoclonal gammapathy (Jensen et al, 2020;Lazarian et al, 2020;Lopez et al, 2020) and 2 had Evans syndrome (Li et al, 2020;Wahlster et al, 2020). Later, it was stated that AIHA could concern 12% of the subgroup of anemic COVID-19 patients (Algassim et al, 2021). Fourteen additional patients were described: five with paroxysmal nocturnal hemoglobinuria (Kulasekararaj et al, 2020;Pike et al, 2020) and 9 with previously undiagnosed glucose-6-phosphate dehydrogenase (G6PD) deficiency uncovered in context of acute hemolysis (Aguilar and Averbukh, 2020;Beauverd et al, 2020;De Franceschi et al, 2020;Kuipers et al, 2020;Maillart et al, 2020;Palmer et al, 2020;Sasi et al, 2020;Sgherza et al, 2020;Lopes et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these patients with thrombocytopenia were diagnosed by exclusion and had a favorable response to corticosteroids, IVIG, and even thrombopoietin receptor agonists. Positive direct Coomb's test was shown in 13% of 267 anemic COVID-19 patients and 46% of the other 113 COVID-19 patients (114,115). Furthermore, both warm and cold AIHA have been reported in COVID-19 patients and most of them recovered spontaneously (116)(117)(118)(119)(120)(121)(122).…”
Section: Hematological Manifestationsmentioning
confidence: 92%
“…Accordingly, patients developing a positive DAT might be more at risk for admission in the ICU. This inding can be linked to the study showing that a lower hemoglobin level at admission is associated with a more severe disease evolution [6].…”
Section: Alloadsorptionmentioning
confidence: 86%
“…A growing number of complications have been associated with the virus, notably the occurrence of AIHA, as well as other autoimmune disorders. A study has shown a correlation between the hemoglobin level at hospital admission and the severity of the coronavirus disease 2019 (COVID-19) [6]. This highlights the clinical importance of inding the cause and correctly treating the anemia occurring in these patients.…”
Section: Introductionmentioning
confidence: 99%